IMPACT OF SOCIAL MEDIA USAGE ON SOCIAL, ACADEMIC AND PROFESSIONAL LIVES OF MEDICAL STUDENTS - Dr. Nagma Bansal; Dr. Amita Jindal; Dr. Raj Kumar; Savi Jindal; Dr. Kamalpreet Kaur (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Social media has become an integral part of the lives of the medical students. Students spend more than usual hours on social networking and it affects their social, personal and professional lives.Objectives: The objective of the study was to assess the pattern of usage of social media and its impact on the social, professional and academic lives of medical students.Study design:  It was a cross sectional questionnaire based study.Material and methods: The study was conducted on 246 MBBS students. The data was collected with the help of questionnaire designed for gathering the effect of social media apps on social, academic and professional lives of students.Results: Majority of the students (64.8%) had been using these apps for more than two years. Overall opinions on impact of social media usage were mixed. 87.6% of the participants believed that social media applications are effective communication applications. 76.4% reported that it decreased their concentration in studies.Conclusion:  Balanced use of social media is essential for maintaining academic responsibilities. While platforms such as whattsapp and facebook can provide valuable opportunities for recreation and education, excessive use may contribute to social networking site addiction, adversely affecting students academic performance and professional development.